Kemampuan Pemecahan Masalah Matematis Mahasiswa Pendidikan Fisika Ditinjau dari Kepribadian Tipe Myers-Briggs - Wahidaturrahmi Wahidaturrahmi; Baidowi Baidowi (Mandalika Mathematics and Educations Journal, 2022)
Mathematics is a universal science that underlies the development of modern technology, so that mathematics has an important role in various scientific disciplines, one of which is physics. Physics students need mathematical skills to understand physics concepts. The purpose of this research is to analyze the mathematical problem solving abilities of physics education students in terms of the Myers-Briggs personality type. This type of research is quantitative. The population is physics education students at the Mataram University of the 2022/2023 academic year. The research instrument are a questionnaire to measure personality types (artisans, guardians, idealists, and rationals) and mathematics tests (essay questions). Descriptively, most students have not been able to make conclusions from the solutions obtained. Inferentially, the average math scores of rational personality students were higher than the average math scores of guardian, artisan, and idealist personality students. Thus, students of physics education of rational types have better mathematical problem solving abilities than guardian, artisan, and idealist types.